2013
DOI: 10.5152/ucd.2013.1955
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality and morbidity in peritonitis in a developing country

Abstract: Objective: Generalized peritonitis is still a common emergency managed by most general surgeons throughout the world. If the outcome in these patients can be correctly predicted, then better management can be instituted to those patients in need. This study aims to identify factors in patients with peritonitis which have a significant bearing on morbidity and mortality. These factors could be later used to predict the outcome in patients with generalized peritonitis. Material and Methods:A total of one hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
14
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 15 publications
9
14
3
Order By: Relevance
“…10 Mean APACHE II Score in present study was 13.13±8.62. Mean APACHE II Score among survivor was 10.99 while among non-survivor it was 25.27.…”
Section: Discussionmentioning
confidence: 43%
“…10 Mean APACHE II Score in present study was 13.13±8.62. Mean APACHE II Score among survivor was 10.99 while among non-survivor it was 25.27.…”
Section: Discussionmentioning
confidence: 43%
“…But in this study the lower complications in the elderly probably was affected by small number of participants in the elderly group. This study found other indicators for complications include female 61.5%, high PR 48.6% ,purulent peritoneal uid 51.2%, GIT perforation 51.3%, gangrenous bowel 71.4% ,TLC (less than 4 × 10 9 /L) 66.7%, sodium less than 135 mmol/L (50%), all these were not statistically signi cant when compared to previous study done by Khan et al which reported signi cant association with low Hb 36%,Sodium level less than 135 mmol/L (42.9%) and purulent peritoneal uid 38.7% (5).…”
Section: Discussioncontrasting
confidence: 52%
“…Hypokaelemia of less than 3.8 mmol/L was signi cantly related to complications contrary to ndings by Khan et al,. in India where Potassium levels had no relation at all to complications (5). However, despite the difference in nding between the current and that reported by Khan et al, Potassium is still one of the parameters in the Acute Physiology and Chronic Health Evaluation (APACHE) scoring system to predict the outcome.…”
Section: Discussionmentioning
confidence: 56%
“…Currently in developing countries the mortality due to peritonitis is reported to be between 13-43%, thus becoming the dominant cause of death due to surgical infections despite the great progress in intensive care support, antimicrobial therapy and surgical techniques. Timely prognostic evaluation of peritonitis will not only provide desirable categorization of disease severity but also correctly predict the outcome hence more aggressive and better therapeutic management can be instituted [5,6]. In Tanzania a study done at Bugando Medical Centre (BMC) in 2015 showed the overall mortality was 15.46% with overall postoperative complications of 36.08% [5,6].…”
mentioning
confidence: 99%